Politisasi Birokrasi dalam Pilkada Banten 2006 - Hamid, Abdul (Jurnal Ilmu Administrasi Negara, 2012)
This study analyzed the involvement of bureaucracy as a political actor in2006 Governor Direct Election (Pilkada) of Banten Province. The main goal of the studyis to capture a comprehensive picture about the involvement of bureaucracy actor inPilkada. This research used qualitative method. The data were collected through in-depthinterview and document analysis. Th eresult of this study find that: First, governor directelection has been fertile soil for paternalism culture in bureaucracy. Second, before andafter election, the strategic position in bureaucracy tended to be positioned as the giftsfor loyal persons. It became pulled factor to bureaucrats to be the candidate supportersin Pilkada. On the other hand, many persons in strategic positions were lost theirpositions due to political reasons. The other phenomenon was how the “outsiderbureaucracy” could show their power to make decision and allocate state resources tothe candidate‟s (mostly incumbent) interests.